Impacts of Remittance on Migrants’ Households in Agrarian Societies of Sindhuli, Nepal - Thapaliya, Krishna Prasad; Pyakuryal, Kailash Nath; Devkota, Durga; Panta, Dhrub; Ghimire, Anita (Journal of Agriculture and Forestry University, 2025)
Nepal experienced a notable surge in remittance volume in the fiscal year 2021/22 reaching its highest proportion in GDP over the past six years. This study aimed to understand the impacts of remittance on the agrarian community and the livelihoods of these households. This research was conducted in 2021 by employing a mixed-methods approach, incorporating both qualitative and quantitative methodologies. Simple random sampling was used to select 350 households from seven different wards of Marin Rural Municipality. Quantitative data were collected through face-to-face interviews using a structured questionnaire. Additionally, qualitative information was collected through Key Informant Interviews (KII) from 21 purposively selected participants. The findings revealed that nearly 95% of households primarily depend on remittances for their income, with 96.9% using the sum for debt repayment and 78.6% for their children’s education. Furthermore, the findings indicated that remittances significantly impact various aspects of individuals’ lives in the research area, including food sufficiency, healthcare access, and community involvement. With a substantial impact on debt repayment, savings, and children’s education, remittances significantly contribute to the socio-economic landscape, positively affecting food sufficiency, healthcare access, and overall consumption for families in the agricultural communities of Sindhuli district of Nepal. Effective strategies and concrete plans are thus required to promote safe and dignified migration in the days to come.